Ilmu I’rab Sebagai Alat Pemahaman Konteks Al Qur’an Dalam Surat Al-Hujurat Ayat 10 - Yumna Fathiyah Nabilah; Intan Nazmi Nurlaila; Nadia Fitri Yani; Tika Muslikha Risqiani (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the role of the science of i'rab as the main tool in understanding the context of the Qur'an, especially in Surah Al-Hujurat verse 10. This verse contains an important message about the brotherhood of Muslims and the command to improve relations between fellow believers and to be pious to Allah. Through the analytical approach of the science of i'rab, this study traces the function and position of words in the sentences of the verse to obtain a precise and contextual understanding. The results of the analysis show that the understanding of i'rab greatly determines the meaning and context of the verse, so that it can avoid misinterpretations that have the potential to change the message of Islamic teachings. I'rab plays a role as a grammatical instrument that maintains the integrity and accuracy of the meaning of revelation, and strengthens the social and spiritual context in the Qur'an. This study confirms that mastery of the science of i'rab is an essential need for interpreters, researchers, and students of the Qur'an to understand the holy text comprehensively and accurately.